The Impact of Deposit Dollarization on Financial Deepening - Court Monteverde, Eduardo (2012)
Banks in highly dollarized economies face risks that significantly affect their ability to perform their financial intermediation role. In these economies, dollarization plays a dual role: on one hand, it provides a hedging instrument protecting the value of savings and, on the other hand, it generates currency mismatch on banks’ balance sheets and increases default risk. Through these effects deposit dollarization can impact credit extension. This paper investigates the role of deposit dollarization on the financial depth of 44 emerging market economies. Findings suggest that deposit dollarization has a consistent and negative impact on financial deepening, except in high-inflation economies.